PENGEMBANGAN SISTEM INFORMASI KEUANGAN HIMA BERBASIS WEB - Pramudya Azis; Faiza Rini; Rahayu Trisetyowati Untari (Smart Education, 2026)
Abstract: This study aims to develop a web-based financial information system for the Student Association (HIMA) of the Information Technology Study Program at Universitas PGRI Sumatera Barat. The research was motivated by the limitations of manual financial recording, which may cause data inaccuracies, document loss, and delays in reporting. The development process applied the System Development Life Cycle (SDLC) using the Waterfall model, including requirement analysis, system design, implementation, testing, deployment, and maintenance. System feasibility was evaluated through beta testing involving system experts and users. The results indicate that the system achieved an average score of 90.13% from experts and 88.06% from users, both categorized as very good. These findings demonstrate that the developed system fulfills functional and non-functional requirements and is feasible for implementation. The system contributes to improving efficiency, transparency, and accuracy in managing organizational financial data. Keywords: Financial Information System; Web-Based System; Student Association; SDLC; Waterfall Model. Abstrak: Penelitian ini bertujuan untuk mengembangkan Sistem Informasi Pencatatan Keuangan HIMA berbasis web pada Program Studi Teknologi Informasi Universitas PGRI Sumatera Barat. Pengembangan dilakukan karena proses pencatatan keuangan masih dilakukan secara manual sehingga berpotensi menimbulkan kesalahan data, kehilangan arsip, dan keterlambatan dalam penyusunan laporan. Metode yang digunakan adalah System Development Life Cycle (SDLC) dengan model Waterfall yang meliputi analisis kebutuhan, perancangan sistem, implementasi, pengujian, deployment, dan pemeliharaan. Evaluasi sistem dilakukan melalui pengujian beta oleh tenaga ahli dan pengguna. Hasil pengujian menunjukkan nilai rata-rata sebesar 90,13% dari tenaga ahli dan 88,06% dari pengguna dengan kategori sangat baik. Hasil tersebut menunjukkan bahwa sistem telah memenuhi kebutuhan fungsional dan nonfungsional serta layak digunakan. Implementasi sistem ini mampu meningkatkan efisiensi, transparansi, dan akurasi dalam pengelolaan keuangan organisasi mahasiswa.. Kata kunci: Sistem Informasi Keuangan; Berbasis Web; HIMA; SDLC; Waterfall